2018
DOI: 10.3892/ol.2018.8312
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of histone lysine acetylation and proteomic changes in EC109 cells treated with the histone deacetylase inhibitor FK228

Abstract: Abstract. FK228 is a selective inhibitor of histone deacetylases that exhibits marked antitumor activity in cancer cells and xenograft models. However, the effect of FK228 on the global profile of histone lysine acetylation and the proteome of EC109 cells remains poorly understood. The present study aimed at analyzing histone lysine acetylation and identifying the proteomic changes in EC109 cells following treatment with FK228, using the stable isotope labelling by amino acids in cell culture technique and a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The desalted peptides were analyzed using an EASY-nLCTM 1200 UHPLC system (ThermoFisher) coupled to an Orbitrap Q Exactive HF-X mass spectrometer (ThermoFisher) in the data-dependent acquisition (DDA) mode [24]. Briefly, peptides in 0.1% FA (Formic acid) were injected onto a Acclaim PepMap100 For DDA, the Q-Exactive HF-X mass spectrometer was operated in positive mode with spray voltage of 2.3 kV and the capillary temperature was 320°C.…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%
“…The desalted peptides were analyzed using an EASY-nLCTM 1200 UHPLC system (ThermoFisher) coupled to an Orbitrap Q Exactive HF-X mass spectrometer (ThermoFisher) in the data-dependent acquisition (DDA) mode [24]. Briefly, peptides in 0.1% FA (Formic acid) were injected onto a Acclaim PepMap100 For DDA, the Q-Exactive HF-X mass spectrometer was operated in positive mode with spray voltage of 2.3 kV and the capillary temperature was 320°C.…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%
“…Enrichment analysis of the molecular functions revealed that the actin-binding and metal-binding proteins were upregulated. Proteins related to oxidoreductase or aldo–ketoreductase activities were downregulated [77].…”
Section: Proteomic and Acetylomic Analysis Of Hdismentioning
confidence: 99%
“…The tryptic peptides were dissolved in 0.1% formic acid (solvent A), directly loaded onto a reversed-phase precolumn (Acclaim PepMap 100; Thermo Fisher Scientific, Inc.). Peptide separation was performed using a reversed-phase analytical column (Acclaim PepMap RSLC; Thermo Fisher Scientific, Inc.) with gradient that comprised of an increase from 6 to 23% solvent B (0.1% formic acid in 98% acetonitrile) over 26 min, 23 to 35% in 8 min and climbing to 80% in 3 min then holding at 80% for the last 3 min, all at a constant flow rate of 400 nL/min on an EASY-nLC 1000 UPLC system [16].…”
Section: Quantitative Proteomic Analysis By Lc-ms/msmentioning
confidence: 99%